Innovation and diversity based organization culture and its effect on competitive advantage - Azlan Amran, Yang Hao, Essia Ries Ahmed, Karpal Singh Dara Singh, (Opción, 2019)
The purpose of this research is to analyze the role of organizational culture in particular innovation and diversity culture towards helping organizations to achieve competitive advantage. The research adopts a quantitative approach, where a set of questionnaire was developed by making necessary adaptations to available scales. As a result, both innovative and diversity based organization culture is positively associated with a competitive advantage and can put organizations towards the path of increasing their competitiveness. In conclusion, the results of the study support the proposed organizational culture types (namely, innovation and diversity) that play a dominant role in achieving competitive advantage.